Comprehensive Quantum Chemical Characterization of the Astrochemically Relevant HCnH Chain Family: An Attempt to Aid Astronomical Observations. Issue 8 (22nd June 2022) - Bâldea, Ioan
Abstract: In this paper, the results of a comprehensive theoretical investigation of neutral HC n H 0 and charged HC n H ± chains are reported using state‐of‐the‐art compound model chemistries (W1BD, G4, CBS‐QB3, CBS‐APNO, CBS‐4M) and single point methods (including "gold standard" CCSD(T)). The properties envisaged include electronic and chemical bonding structure data, enthalpies of formation, adiabatic and vertical ionization (IP), and electron attachment (EA) energies, gas phase acidities, C−H bond strengths, and chain "deprotecting" (HC n H → H + C n + H) energies. The best theoretical estimates based on composite models reported here for the various properties investigated agree with the available experimental data and are better than all previous theoretical estimates. To exemplify, for the enthalpies of formation, the G4 composite model achieves a RSMD (root square mean deviation) of 0.28 kcal mol −1 and a MUD (maximum unsigned deviation) of 0.45 kcal mol −1 . Most importantly from the astrochemical perspective, it is predicted that the stable HC n H − anions with n ≤ 8 $n\le 8$ are nonlinear. Having sufficiently large dipole moments, the anion HC n H − cis conformers are potential candidates for detection in space via rovibrational spectroscopy. Abstract : Results for HC n H chains reported here comprise electronic structure and chemical bonding data, ionization and electron attachment energies, chemical reactivity indices as well as a variety of thermochemical properties (triplet–singlet energy splitting, enthalpies of formation, gas‐phase acidities, enthalpies of dissociation, and anion cis – trans isomerization). Some thereof are new values of thermodynamic quantities which have to be measured yet.